Dynamic Nuclear Polarization Fast Field Cycling Method for the Selective Study of Molecular Dynamics in Block Copolymers. Issue 17 (1st August 2017) - Gizatullin, Bulat; Neudert, Oliver; Stapf, Siegfried; Mattea, Carlos
Abstract: Dynamic nuclear polarization (DNP) is one of the most useful methods to increase sensitivity in NMR spectroscopy. It is based on the transfer of magnetization from an electron to the nuclear spin system. Based on previous work that demonstrated the feasibility of integrating DNP with fast field cycling (FFC) relaxometry and the possibility to distinguish between different mechanisms, such as the Overhauser effect (OE) and the solid effect (SE), the first FFC study of the differential relaxation properties of a copolymer is presented. For this purpose, concentrated solutions of the polystyrene‐ block ‐polybutadiene‐ block ‐polystyrene (SBS) triblock copolymer and the corresponding homopolymers were investigated. T 1 – T 2 relaxation data are discussed in terms of molecular mobility and the presence of radicals. The DNP selective data indicate a dominant SE contribution to the enhancement of the NMR signal for both blocks of the triblock copolymer and for the homopolymer solutions. The enhancement factors are different for both polymer types and in the copolymer, which is explained by the individual 1 H T 1 relaxation times and different electron–nucleus coupling strength. The T 1 relaxation dispersion measurements of the SE enhanced signal were performed, which led to improved signal‐to‐noise ratios that allowed the site‐specific separation of relaxation times and their dependence on the Larmor frequency with a higher accuracy. Abstract : Selective dynamic nuclear polarization : Spin‐lattice relaxation dispersion measurements of the dynamic nuclear polarization (DNP)‐enhanced signal of triblock copolymers are performed and lead to improved signal‐to‐noise ratios that allow the site‐specific separation of relaxation times (see picture) and their dependence on the Larmor frequency with a higher accuracy.